منصات خدمات المکتبات التعاونية مفتوحة المصدر:دراسة حالة لمنصة مستقبل المکتبات الانفتاحية (فوليو Folio ) (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims to open source library services platforms, especially Folio platform; therefore, it seeks to identify the new generation of open source library service platforms, relying on the case study methodology to examine and analyze everything related to the emergence and development of the Folio platform, as well as studied of technical and functional characteristics. Due of importance of these new generations of automated systems, because of the acceleration of development and the short period of time between them. The study concluded that the Folio platform is still in its first start, which resulted in many things, including: the limited implementation in the world, followed by the lack of clarity of the image in case that it was applied in the Arab environment, and despite all that the platform was characterized by its many the functional and technical features and capabilities are unique form other library service platforms. This study also recommended that it is necessary to go towards participation in the Folio platform as a fertile field for investment in it by specialized companies and even professional societies and federations to contribute in development in order to have an active role in the field of developing automated systems globally as an influential field in the librarianship, especially the open source products.